PERTANGGUNGJAWABAN PIDANA PARTAI POLITIK SEBAGAI KORPORASI DALAM TINDAK PIDANA PENCUCIAN UANG DARI HASIL TINDAK PIDANA KORUPSI DI INDONESIA - Yesi Mutia Dini; Mexsasai Indra; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Related to the crime of money laundering committed by political parties, as a legal entity a politicalparty can be held to hold criminal responsibility for what it has done. It can be said that a corporation hascommitted a crime if the criminal offense is carried out by a corporate executive or employee who is stillwithin the scope of his authority, and intra-vires in the sense that it is still in part of the corporation'sintentions and objectives, and acts for corporate purposes. The purpose of this thesis is first to find out howto determine errors in political parties as corporations that commit a crime in the crime of moneylaundering as a result of corruption in Indonesia. Second, to find out the form of criminal liability ofpolitical parties as corporations in criminal acts of money laundering resulting from criminal acts ofcorruption in Indonesia.From the results of the research conducted there are three main things that can be concluded. First,determining the mistakes of the corporation can be done by looking at the intentions or negligence of thepolitical party administrators. This form of error is not individual but is collective and the corporationreceives the benefits of the crime. Therefore, it can be stated that the corporation (political party) is blamed.Second, based on the theory of direct corporate liability and functional actors, corporations can be held tohold criminal liability insofar as it is known to the political party management to commit the crime for andon behalf of the corporation itself (political party). The author's suggestion, First, is expected to the Houseof Representatives and the President to explicitly regulate the criminal responsibility of the corporation bothin the Act on crime of money laundering and corruption. Second, it is hoped that law enforcement officialswill be more courageous in disclosing and taking action against the involvement of political parties in theuse of funds that are sourced or reasonably suspected of money laundering.Keywords: Accountability of Political-Corporations-Corporations-Money Laundering-Corruption Crimes